PPARγ as an E3 Ubiquitin-Ligase Impedes Phosphate-Stat6 Stability and Promotes Prostaglandins E2-Mediated Inhibition of IgE Production in Asthma - Wu, Jia; Wang, Yan; Zhou, Yu; Wang, Yuqing; Sun, Xiaowan; Zhao, Ye; Guan, Youfei; Zhang, Yu; Wang, Wei (Frontiers in Immunology, 2020)
Increased serum IgE level is one of the features of allergic asthma. It is reported that IgE production can be enhanced by E-prostanoid 2 (EP2) receptor of prostaglandin E2 (PGE2); however, whether E-prostanoid 4 (EP4) receptor (encoded by Ptger4) has a unique or redundant role is still unclear. Here, we demonstrated the mice with B cell-specific deletion of the EP4 receptor (Ptger4fl / fl Mb1cre+/-) showed their serum levels of IgE were markedly increased. A much more severe airway allergic inflammation was observed in the absence of EP4 signal using the OVA-induced asthma model. Mechanistic studies demonstrated that the transcription levels of AID, GLTε, and PSTε in EP4-deficient B cells were found to be significantly increased, implying an enhanced IgE class switch. In addition, we saw higher levels of phosphorylated STAT6, a vital factor for IgE class switch. Biochemical analyses indicated that inhibitory effect of EP4 signal on IgE depended on the activation of the PI3K-AKT pathway. Further downstream, PPARγ expression was up-regulated. Independent of its activity as a transcription factor, PPARγ here primarily functioned as an E3 ubiquitin-ligase, which bound the phosphorylated STAT6 to initiate its degradation. In support of PPARγ as a key mediator downstream of the EP4 signal, PPARγ agonist induced the down-regulation of phospho-STAT6, whereas its antagonist was able to rescue the EP4-mediated inhibition of STAT6 activation and IgE production. Thus, our findings highlight a role for the PGE2-EP4-AKT-PPARγ-STAT6 signaling in IgE response, highlighting the therapeutic potential of combined application of EP4 and PPARγ agonists in asthma.